Una nota desconocida de Rafael Dieste sobre Adolfo Pastor en la revista porteña Pensamiento español (1942). Tensiones y conflictos en el exilio republicano en Argentina - Núñez, César (El Colegio de México, 2018)
This article presents a previously unstudied note by Rafael Dieste regarding an exhibition of drawings and engravings by the Uruguayan artist Adolfo Pastor at the Viau Gallery in Buenos Aires. The note, published in Pensamiento español in 1942, was Dieste’s third contribution to this journal, edited by a group of Spanish exiles. The article offers precise bibliographic information about the two poems that Dieste published in the journal; both were included in the first volume of his Obras completas, but little else was previously known about them. The article also describes the journal’s most immediately recognizable characteristics linking it to the goal of re con structing the cultural world of the exiles.